Hubungan Tingkat Kemandirian Lansia dengan Perilaku Personal Hygiene - Hakim, Adinda Maulida; Hartati, Elis (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between the level of independence of the elderly and personal hygiene behavior. This research method uses a correlational descriptive quantitative study approach using bivariate Spearman rank analysis. Data collection used the Katz Index questionnaire and personal hygiene questionnaire. The research showed that 90.2% of older people were wholly independent, and 63.9% of older people were good at personal hygiene. The results of the Spearman rank test show a relationship between the level of independence of the elderly and personal hygiene behavior with a value of p = 0.000. In conclusion, older people are in good condition. They can carry out all their activities independently and have good personal hygiene behavior. There is a relationship between the level of independence of the elderly and individual hygiene behavior. Keywords: Elderly, Personal Hygiene, Level of Independence